A Textbook of Business Economics - Pareek, Saroj (Sunrise Publishers & Distributors, 2012)
"This book is intended to explain in non-technical language, the economic concepts, tools of analysis, their relevance in management decision-making and also the influence of economic environment on management decisions. To facilitate an easy understanding of the subject, the timely help of illustrations, examr::es, diagrams, tables and charts has been taken, Important terms relevant to the business economics are given in a separate chapter. To my publisher, I am grateful for publishing the book with due care and skill in a very short time. I shall be thankful to the readers for pointing out discrepancies and errors in the text, which I hope to rectify in the next edition of the book. Suggestions for further improvement of this book will be highly appreciated."